Diversity and Evolution of Pigment Types in Marine Synechococcus Cyanobacteria. (11th March 2022) - Grébert, Théophile; Garczarek, Laurence; Daubin, Vincent; Humily, Florian; Marie, Dominique; Ratin, Morgane; Devailly, Alban; Farrant, Gregory K; Mary, Isabelle; Mella-Flores, Daniella; Tanguy, Gwenn; Labadie, Karine; et al.
Abstract: Synechococcus cyanobacteria are ubiquitous and abundant in the marine environment and contribute to an estimated 16% of the ocean net primary productivity. Their light-harvesting complexes, called phycobilisomes (PBS), are composed of a conserved allophycocyanin core, from which radiates six to eight rods with variable phycobiliprotein and chromophore content. This variability allows Synechococcus cells to optimally exploit the wide variety of spectral niches existing in marine ecosystems. Seven distinct pigment types or subtypes have been identified so far in this taxon based on the phycobiliprotein composition and/or the proportion of the different chromophores in PBS rods. Most genes involved in their biosynthesis and regulation are located in a dedicated genomic region called the PBS rod region. Here, we examine the variability of gene content and organization of this genomic region in a large set of sequenced isolates and natural populations of Synechococcus representative of all known pigment types. All regions start with a tRNA-PheGAA and some possess mobile elements for DNA integration and site-specific recombination, suggesting that their genomic variability relies in part on a "tycheposon"-like mechanism. Comparison of the phylogenies obtained for PBS and core genes revealed that the evolutionary history of PBS rod genes differs from the core genome and is characterized by the co-existence of different alleles and frequent allelic exchange. We propose a scenario for the evolution of the different pigment types and highlight the importance of incomplete lineage sorting in maintaining a wide diversity of pigment types in different Synechococcus lineages despite multiple speciation events.